Sintesis Ferroelektrik BaZrxTi1-xO3 Dengan Variasi Zirkonium Terhadap Struktur Kristal dan Konstanta Dielektrik - Yunita Subarwanti; Erni Mariana (Jurnal Teori dan Aplikasi Fisika, 2021)
This study aims to determine influence addition Zr against the crystal structure and dielectric constant; and to know the influence of variations temperature sintering on addition mole Zr. Barium Zirconium Titanate (BaZrxTi1-xO3) have been made with variation zirconium (Zr) 1%, 5%, 10%, and 20% by solid state reaction method, that is blanded BaTiO3, TiO2 and ZrO2 powder. BaZrxTi1-xO3 powder is printed with die pressing and press hidrolik, then the samples were sintered by furnace at 900oC and 1000oC with holding time 2 hours. Characterization of samples use X-Ray Diffraction and Resistance Capacitance Inductance (RCL meter). Based on result obtained, the larger Zr content cause dielectric constant decreasing because crystal structure have been change from tetragonal (Zr = 1% and 5%) to cubic (Zr = 10% and 20%). The result from X-Ray Diffraction already match with data base ICDD no#360019. Measurement of dielectric constant (K) performed in the frequency range 1 kHz to 100 kHz and the highest value at Zr content 1%, because The dielectric constant decreasing with the larger Zr content. The maximum dielectric constant is obtained at mol Zr 5% and sintering temperature 1000oC, that is 150. The minimum dielectric constant is obtained at mol Zr 20% and sintering temperature 900oC, that is 62.